The Teutonic manor in Benowo (Poland), its origin, history and significance in the light of historical and architectural analysis - Karol Czajka-Giełdon (Ochrona Dziedzictwa Kulturowego, 2023)
This paper deals with the history of the former Teutonic manor in Benowo (German name: Bönhof) in relation to its spatial arrangement. The first part presents the source historical messages relating to this place and an attempt is made to read them again based on the relevant available research by historians and archaeologists regarding the beginnings of the activity of the Teutonic Order in the Prussian land. The available archival cartography concerning the location of the manor house is also described. The following section presents new findings related to the use of modern land registration techniques – aerial and satellite photos and LIDAR airborne laser scanning. The result of the research is the indication of the character and shape of the buildings and the exact location of some of the objects included in the farm buildings, as well as the formulation of a hypothesis regarding the land forms existing in their immediate vicinity.